Acute appendicitis in a patient after a uterus transplant: A case report - Kristek, Jakub; Kudla, Michal; Chlupac, Jaroslav; Novotny, Robert; Mirejovsky, Tomas; Janousek, Libor; Fronek, Jiri (World journal of clinical cases, 2019)
BACKGROUND: Acute appendicitis in a solid organ transplant recipient is a rare occurrence, and experience remains limited. Appendicitis in uterine transplant recipients has never been reported. Immunocompromised patients with acute abdomen often present late and with attenuated symptoms. The differential diagnosis in a transplanted patient is broad and challenging due to possible existing complications associated with the graft, effects of immunosuppression, and altered anatomical relations. CASE SUMMARY: A 26-year-old woman suffering from absolute uterine factor infertility received a uterus transplant. In the post-transplant period, she suffered from leukopenia and recurrent acute cellular rejection. Her compliance was suboptimal. She travelled to an exotic destination despite the physician's recommendation not to do so. Following her vacation, she presented with abdominal discomfort, nausea and diarrhoea. There was no sign of acute abdomen; the abdominal ultrasound was negative on day 0. Clostridium difficile colitis was verified and treated with perorally administered vancomycin. On day 4, the discomfort changed to pain; the ultrasound scan revealed a finding suggestive of appendicitis. Surgical exploration revealed perforated appendicitis, and appendectomy was performed. From a surgical point of view, the patient's follow-up was uneventful. The patient underwent a successful embryo transfer 6 months after the appendectomy. The patient gave birth to a healthy boy at the 35th week of gestation. CONCLUSION: A high index of suspicion of an atypical course and symptomatology of acute abdomen should be maintained in immunosuppressed patients.
Keywords: Uterus; Acute abdomen; Organ transplantation; Noncompliance; Case report; Differential diagnosis; Colitis